DEVELOPMENT OF ISLAMIC LAW (FIQH) THROUGH THE MAQASID AL-SYARI'AH APPROACH - Rohani (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
The discussion about maqashid al-syari'ah or the purpose of Islamic law is an important discussion in Islamic law that has not escaped the attention of scholars and experts in Islamic law. Basically, Shari'a and religion cannot be understood partially. However, it must be seen as a whole as an inseparable whole. Religious goals and sharia goals can be categorized into general goals and specific goals. If all the commands and prohibitions of Allah are carried out in the Qur'an, as well as the orders and prohibitions of the Prophet SAW in the sunnah which are formulated in fiqh, it will be seen that all of them have a specific purpose and nothing is in vain. All of them have a deep wisdom, namely as a mercy for mankind, as confirmed in several verses of the Qur'an about the purpose of the Prophet Muhammad was sent. Grace for all nature in the verse is defined by the benefit of the people. Meanwhile, in simple terms, benefit can be interpreted as something that is good and can be accepted by common sense. It is accepted that reason contains that reason can know and understand the motives behind the determination of a law, namely because it contains benefits for humans, either by explaining the meaning itself by God or by means of rationalization